2021
DOI: 10.21203/rs.3.rs-1075613/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Timely initiation of breastfeeding and associated factors among mothers with vaginal and cesarean deliveries in public hospitals of Addis Ababa

Abstract: Background WHO and UNICEF recommend breastfeeding to be initiated within the first hour of birth. It is possible to initiate breastfeeding within an hour of birth regardless of the method of delivery. Despite this, the practice of timely initiation of breastfeeding remains low in Ethiopia with both delivery modalities. Therefore, this study aims to compare timely initiation of breastfeeding and associated factors with cesarean and vaginal deliveries in public hospitals of Addis Ababa, 2021. Methods and materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
3
2
0
Order By: Relevance
“…The magnitude of timely initiation of breastfeeding in this study was consistent with the finding of studies conducted in the south Gondar zone, Ethiopia (51.9%) [15], and Addis Ababa, Ethiopia (51.2%) [17]. However, this finding was lower than the result of studies done in Dessie city, Ethiopia (57%) [16], Malaysia (73.7%) [22], and WHO global survey (57.6%) [23].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The magnitude of timely initiation of breastfeeding in this study was consistent with the finding of studies conducted in the south Gondar zone, Ethiopia (51.9%) [15], and Addis Ababa, Ethiopia (51.2%) [17]. However, this finding was lower than the result of studies done in Dessie city, Ethiopia (57%) [16], Malaysia (73.7%) [22], and WHO global survey (57.6%) [23].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the odds of timely initiation of breastfeeding were 3.07 times higher among women who got assistance from health professionals for timely initiation of breastfeeding when compared with women who didn't get assistance from health professionals. This finding was supported by the study done in the south Gondar zone, Ethiopia [15], Addis Ababa, Ethiopia [17], Bangladesh [35], and Uganda [36]. This might be due to assistance from obstetric care providers for proper attachment and positioning to initiate breastfeeding within one hour of delivery, mothers get emotional well-being and inspiration, which help them to initiate breastfeeding within one hour of delivery [37].…”
Section: Plos Onesupporting
confidence: 53%
See 1 more Smart Citation
“…Likewise, regarding type of delivery, mothers who delivered vaginally were 0.461 times more likely to initiate breastfeeding than mothers who delivered by caesarean section. The findings is supported by a comparative cross-sectional study conducted in a hospital of Ethiopia, Timely breastfeeding initiation was 79 (51.2%) and 123 (80%) for cesarean and vaginal deliveries, with a vaginal delivery (AOR= 5.50, 95% CI: 1.83-16.57) and multiparity (AOR= 2.14, 95% CI: 1.02-4.50), was significantly associated with timely initiation of breastfeeding 19.…”
supporting
confidence: 57%
“…Regarding pre lacteal feeding, only 18.9% of respondents using pre-lacteal feeding to their children which is similar to the study conducted in Ethiopia revealed that 24.2% mothers give prelacteal feed. 19 Findings of the present study revealed that socioeconomic status of the respondents was significantly associated with timely initiation of breast feeding (p=0.029). The finding of the study was supported by study done in North-Central Nigeria the relationships between the timely initiation of breastfeeding and economic status was statistically significant .…”
Section: Discussionmentioning
confidence: 53%